Image of Joseon Women in the Eyes of Europeans in the 19th Century: Truth and Misunderstanding - Han, Boram (International Journal of Korean Humanities and Social Sciences, 2024)
This research examines the depiction of Joseon women in the eyes of 19th-century European visitors, juxtaposing it with historical records from Joseon itself, particularly Sabeobpumbo. European accounts, influenced by Orientalism, often portrayed Korean women as oppressed, passive figures. However, these narratives also captured moments where women exerted agency and autonomy, challenging stereotypes of submission. Through comparative analysis of European travelogues and Sabeobpumbo, the study highlights that women in Joseon played active roles in family and community life, often stepping beyond traditional boundaries. This nuanced exploration aims to reveal the complexities of women's lives in Joseon, challenging both contemporary and modern misconceptions.